Characteristics and outcomes of over 300,000 patients with COVID-19 and history of cancer in the United States and Spain - Roel, E; Pistillo, A; Recalde, M; Sena, AG; Fernández-Bertolín, S; Aragón, M; Puente, D; Ahmed, W-U-R; Alghoul, H; Alser, O; Alshammari, TM; Areia, C; et al. (American Association for Cancer Research, 2021)
Background: We described the demographics, cancer subtypes, comorbidities, and outcomes of patients with a history of cancer and coronavirus disease 2019 (COVID-19). Second, we compared patients hospitalized with COVID-19 to patients diagnosed with COVID-19 and patients hospitalized with influenza.